Nitrogen or Sulfur Starvation Differentially Affects Phycobilisome Degradation and Expression of the nblA Gene in Synechocystis Strain PCC 6803 - Richaud, Catherine (American Society for Microbiology, 2001)
Nitrogen (N) limitation in cyanobacteria is well documented: a reduced growth rate is observed, accompanied by a cessation of phycobiliprotein synthesis and an ordered degradation of phycobilisomes (PBS). This leads to a dramatic bleaching phenomenon known as chlorosis. In Synechococcus strain PCC 7942, bleaching due to PBS degradation is also observed under sulfur (S) or phosphorus (P) limitation, and all three are under the control of the nblA gene product, a 59-amino-acid polypeptide which is overexpressed under N, S, and P starvation (J. L. Collier, and A. R. Grossman, EMBO J. 13:1039–1047, 1994). Cyanobase sequence data for Synechocystis strain PCC 6803 indicate the presence of two tandem open reading frames (sll0452 and sll0453) homologous to nblA. We cloned the two genes, identified a unique 5′ mRNA end suggestive of a single transcription start site, and studied nblA expression under conditions of N or S starvation by Northern hybridization: transcripts were detected only under N starvation (no signal is detected in replete medium or with S starvation), whether nblA1 or nblA2 was used as a probe. Mutations in nblA1 and nblA2 were constructed by insertion of a kanamycin cassette; both mutations were nonbleaching under N starvation. Synechocystis strain PCC 6803 does not bleach under S starvation, consistent with the absence of nblA induction in these conditions. These results were confirmed by analysis of the PBS components: sequential degradation of phycocyanin and associated linkers was observed only under conditions of N starvation. This indicates differences between Synechocystis strain PCC 6803 and Synechococcus strain PCC 7942 in their regulatory and signaling pathways leading to N- and S-starved phenotypes.